Late onset group B streptococcus disease manifesting as acute suppurative parotitis. (2020) - Ujita, Nagisa; Kawasaki, Yu; Matsubara, Kousaku; Kim, Kaya; Naito, Akiyoshi; Hori, Masayuki; Isome, Kenichi; Iwata, Aya; Yamaguchi, Yoshimichi; Chang, Bin
Highlights: Acute suppurative parotitis (ASP) caused by GBS primarily arises from bacteremia. Infectious route of is different between ASP infants by GBS and non-GBS pathogens. ASP should be included in an infectious focus as late-onset GBS disease. Blood cultures are essential for accurate diagnosis and optimal therapy. Abstract: Few patients with acute suppurative parotitis (ASP) due to group B streptococcus (GBS) have been documented. Limited data on clinical and microbiological features and infectious route are available. We present a 21-day-old boy with invasive GBS disease manifesting as ASP. The patient was admitted because of irritability, fever, and erythematous swelling over the right parotid area. No purulent material exuded from the Stensen's duct. Ultrasonography and computed tomography of the neck showed findings indicative of ASP. On the day after admission, blood culture yielded GBS. The isolate was determined as GBS serotype Ia and sequence type-23, and the patient was successfully treated with intravenous ampicillin for 10 days. A review of the literature revealed 11 GBS ASP infants including ours with age at onset between 13 days and 12 weeks. All infants had bacteremia while pus from the Stensen's duct was detected in only one case. This finding remarkably contrasts with ASP caused by pathogens other than GBS, where the infection usually spreads via a retrograde route from Stensen's duct. The present case and literature review indicate GBS ASP primarily arises from bloodstream infection, and that ASP should be included in an infectious focus as late onset GBS disease.